Incidental Renal Infarction on imaging for Abdominal Aortic Aneurysm - Cevdet Donmez; Asma Bitar De Zayas-Enriquez; Hosny Hamza; Humayun Bashir (Journal of the Pakistan Medical Association, 2024)
A 59-year-old man who under surveillance for abdominal aortic aneurysm and peripheral artery disease, was investigated with a CT Angiogram aorta. The CT scan showed an abdominal aortic aneurysm reaching 6.2cm with significant thrombus burden, occluded coeliac artery, occluded left iliac artery, calcified stenosis of the right renal artery and features of chronic renal infarct in the right upper pole. Technetium-99m dimercaptosuccinic acid (Tc-99m DMSA) renal scan was done to document the extent of the infarction and for differential function of the kidneys. Keywords: Renal infarction, Abdominal Aortic Aneurysm, Contrast Enhanced CT, DMSA.